Implementation of Musyarakah Agreement In Profit Sharing Cooperation of Investor In Syariah Finance Business - Efendi Sugianto (Al-Makki Publisher, 2024)
In the era of global economic development, the Islamic financial system has emerged as an alternative for various groups who wish to conduct economic activities in accordance with Islamic principles. This study aims to explore how musyarakah contracts are implemented in investment partnerships between investors and businesses in the Islamic financial sector and identify the factors that influence their successful implementation. This research uses a descriptive qualitative approach to understand and analyze the implementation of musyarakah contracts in profit-sharing partnerships in the Islamic financial sector. Primary data was obtained through semi-structured interviews with Islamic business actors, investors, and Islamic finance practitioners. Secondary data were obtained from relevant literature, such as scientific journals, books, and annual reports of Islamic financial institutions. The results show that musyarakah contracts based on the principles of profit sharing and risk sharing provide benefits for both parties. Investors can actively participate in business management with better transparency, while business actors get additional capital to support business expansion. The implementation of musyarakah contracts has shown positive developments in the Islamic financial sector, especially in Indonesia, where regulations and policies have supported the development of sharia-based businesses. However, there are still challenges related to investors' and businesses' understanding of the agreement mechanism, as well as the need for strict supervision to ensure compliance with sharia principles. This research is expected to contribute to the further development of musyarakah contracts in the Islamic finance sector and strengthen the position of Islamic finance in the global market.